Rice production in Ghana: a multi-dimensional sustainable approach - Danso Ofori, Andrews; Titriku, John Kwame; Xiang, Xing; Charlotte, Appiah; Ahmed, Muhammad Irfan; Zheng, Aiping (Frontiers in Agronomy, 2025)
Rice is a vital crop in Ghana, contributing 15% to the country’s Gross Domestic Product (GDP). However, rice production in the country faces significant challenges, including limited access to water, soil degradation, pest and disease pressures, inefficient pesticide use, and other factors that hinder industry growth. This study employs a multi-dimensional sustainable approach to evaluate rice production in Ghana, focusing on environmental, socioeconomic, and food security impacts. A systematic review of literature from 2000 to 2023 was conducted using databases such as PubMed, Web of Science, and Google Scholar. The study identifies key challenges and gaps in the current production system and emphasizes the urgent need for strategies that focus on sustainability, environmental protection, effective resource management, and socioeconomic advancement. These challenges not only affect the environment but also have serious implications for the country’s socioeconomic development. This study aims to evaluate sustainable rice production in Ghana, considering its environmental, socioeconomic, and food security impacts. The research identifies key challenges and gaps in the current production system and emphasizes the urgent need for strategies that focus on sustainability, environmental protection, effective resource management, and socioeconomic advancement. The study highlights the importance of rice in ensuring food security in Ghana and advocates for yield-focused approaches to sustainably increase production. By promoting environmentally friendly practices, the research seeks to mitigate the negative impacts of rice farming, particularly concerning water usage and soil health. Furthermore, the study underscores the importance of sustainable agribusiness practices, providing valuable insights and recommendations for policymakers, stakeholders, and researchers. These strategies aim to secure a resilient and sustainable rice industry that can support both current and future generations. This review primarily focuses on national-level rice production practices in Ghana and their broader implications for environmental sustainability, socioeconomic development, and food security.